Tradisi Berandam pada Pengantin Melayu di Desa Sanglar, Kecamatan Reteh, Kabupaten Indragiri Hilir - Athaya Khairunnisa; Syefriani Syefriani (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The purpose of this research is to find out about the process of implementing traditions soak in Sanglar Village, this research uses descriptive analysis methods, with a qualitative approach. Meanwhile, the data collection techniques used are observation, documentation and interview techniques. The research subject consisted of 1 person as the resource person, namely Nisah as mak Andam, the result of this research was the implementation of tradition soak to the bride in Sanglar Village, soak has several requirements that must be completed, the process soak there are several stages. Tradition soak has the aim of beautifying the prospective bride and a sign of the bride's readiness to become a wife. Implementation of traditions soak Malay weddings in Sanglar Village are very important so this tradition has been carried out for a long time and is still maintained today by the Malay community in Sanglar Village.